PROFILE OF EARTHQUAKE DISASTER LITERACY IN DISASTER MITIGATION UNDERSTANDING AND ABILITY TO STUDENTS IN KUNINGAN - Prihatini, Sri; Rochman, Chaerul (UIN Sunan Gunung Djati Bandung, 2022)
Physics learning is oriented to the facts contained in natural phenomena in the surrounding environment. An earthquake disaster is a related event involving many physics concepts in terms of processes and other points of view. Indonesia is a region that feels in the ring of the fire zone, which causes several areas in Indonesia to be prone to earthquakes. Therefore, a general and initial description is needed to explain the profile of students' scientific literacy abilities because not a few victims swallowed by the earthquake were educated people. The method used in this research is pre-experimental by distributing questionnaires containing questions related to four aspects of scientific literacy regarding earthquakes and their mitigation efforts. The sample of this research is 30 students in class XI IPA 2 at MAN 1 Kuningan in the 2021/2022 academic year. Overall, the scientific literacy ability of students at MAN 1 Kuningan is still relatively low. The results of this study are expected to be used as a primary reference in making models, media, or teaching and enrichment materials that contain natural earthquake events related to their physical concepts.